The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1128/ec.1.4.626-633.2002
|View full text |Cite
|
Sign up to set email alerts
|

Colletotrichum trifolii TB3 Kinase, a COT1 Homolog, Is Light Inducible and Becomes Localized in the Nucleus during Hyphal Elongation

Abstract: Colletotrichum trifolii is a fungal pathogen responsible for anthracnose disease of alfalfa. Previously, a serine/threonine protein kinase gene from this fungus (TB3), which is a functional homolog of the Neurospora crassa COT1 kinase, has been isolated in our laboratory and appears to be associated with hyphal elongation and branching. In this report we show that light treatment rapidly induces TB3 expression and hyphal branching frequency. Western analysis showed TB3 localization in both the cytoplasm and nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…Vegetative growth of fungi has been reported to be influenced by light, both negatively (Casas-Flores et al, 2006; Ambra et al, 2004;Flaherty & Dunkle, 2005;Schmoll et al, 2005) and positively (Lauter et al, 1998;Chen & Dickman, 2002;Chovanec et al, 2001). On a biochemical level, exposure of Aspergillus ornatus to a pulse of light led to protein phosphorylation and decreased glucose uptake (Hill, 1976), and in the slime mould Physarum polycephalum it stopped glucose consumption, and decreased the accumulation of glucans and D-trehalose (Schreckenbach et al, 1981).…”
Section: Ecological Aspects Of Photostimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Vegetative growth of fungi has been reported to be influenced by light, both negatively (Casas-Flores et al, 2006; Ambra et al, 2004;Flaherty & Dunkle, 2005;Schmoll et al, 2005) and positively (Lauter et al, 1998;Chen & Dickman, 2002;Chovanec et al, 2001). On a biochemical level, exposure of Aspergillus ornatus to a pulse of light led to protein phosphorylation and decreased glucose uptake (Hill, 1976), and in the slime mould Physarum polycephalum it stopped glucose consumption, and decreased the accumulation of glucans and D-trehalose (Schreckenbach et al, 1981).…”
Section: Ecological Aspects Of Photostimulationmentioning
confidence: 99%
“…Some authors have described effects of light on hyphal growth or branching, thereby mostly referring to inhibitory effects (Lauter et al, 1998;Chen & Dickman, 2002;Ambra et al, 2004; Casas-Flores et al, 2004;Flaherty & Dunkle, 2005; Miyake et al, 2005;Idnurm & Heitman, 2005;Brasch & Kay, 2006). For arbuscular mycorrhizal fungi, lowintensity light is also known to induce hyphal branching and the consequent increase of mycelial biomass (Nagahashi & Douds, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The greatest variation in the members of this family is in the N-terminal region, which is of variable length, and differs in the presence and length of glutamine rich tracts. The function of these tracts in this family of proteins is unclear, though they are often associated with transcriptional activation (Gerber et al 1994;Chen and Dickman 2002). N. crassa and other Sordariomycetes have the most closely related genes to the Aspergillus species, but the Aspergillus glutamine tracts are not very extensive compared to the Sordariomycetes.…”
Section: Discussionmentioning
confidence: 97%
“…This difference in localisation is difficult to explain, since there is very little difference in the putative nuclear localisation signal. It was suggested that glutamine-rich N-terminal region of TB3 of C. trifolii is associated with nuclear localisation (Chen and Dickman 2002), though there as yet is no clear correlation between structure/presence of the N-terminal region and localisation in this family. As is the case with CotA, tagged-NDR2 shows a punctate distribution in the cytoplasm, and it was suggested that this might reflect presence of some of this kinase in a subcellular compartment other than the nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…(12). GFP has been used for a number of live-imaging applications with plant pathogens, such as invasion of host plant tissue (Fusarium graminearum [23] and M. oryzae [25]), the dynamics of nuclear movement and division during spore germination (M. oryzae [53], Colletotrichum gloeosporioides [35], and Fusarium oxysporum [41]), translocation of regulatory protein kinases from the cytoplasm to nuclei during development and in response to light and nutrient signals (M. oryzae [1], Colletotrichum trifolii [4], and Mycosphaerella graminicola [38]), and stage-specific expression of effector proteins in the host plants (U. maydis [11] and M. oryzae [33]). …”
mentioning
confidence: 99%